2018
DOI: 10.1155/2018/9458410
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Surface Runoff and Macropore Flow for Slopes under Rainfall Conditions

Abstract: Estimating runoff and infiltration in slopes is essential to predict flooding and landslide triggering. An approach jointly using a dual-permeability model and a kinematic wave model was proposed for integrative analyses of infiltration and surface runoff of rainwater for slopes with macropores in soils subjected to rainfalls. Laboratory tests were conducted to evaluate the performance of the proposed approach. Analyses showed that the presence of macropores greatly facilitates rainwater movement in the slope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Zhu et al [23] established an infiltration runoff model for mountain slopes and conducted field flow production and natural precipitation catchment tests; the experimental results were compared with the model to find that the model can better simulate runoff and infiltration, and the measured and simulated values were in good agreement. Yun Que et al [24] proposed a joint approach using a dual infiltration model and a kinematic wave model, performed laboratory tests and found that the presence of macropores greatly facilitated the movement of rainwater on the slope surface. Chao Zhang et al [25] conducted model experiments to find how the groundwater table, which generates pore water pressure, is affected by infiltration time lag, surface runoff and lateral flow.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [23] established an infiltration runoff model for mountain slopes and conducted field flow production and natural precipitation catchment tests; the experimental results were compared with the model to find that the model can better simulate runoff and infiltration, and the measured and simulated values were in good agreement. Yun Que et al [24] proposed a joint approach using a dual infiltration model and a kinematic wave model, performed laboratory tests and found that the presence of macropores greatly facilitated the movement of rainwater on the slope surface. Chao Zhang et al [25] conducted model experiments to find how the groundwater table, which generates pore water pressure, is affected by infiltration time lag, surface runoff and lateral flow.…”
Section: Introductionmentioning
confidence: 99%
“…Increased precipitation events associated with extreme weather conditions affect the stability of slopes and can lead to a variety of geoenvironmental hazards [3,4]. Consequently, shallow landslides may often occur within the vadose zone under unsaturated soil conditions [5][6][7]. The prediction of flow in transient conditions is important in engineering practice while considering the stability of unsaturated soil slopes [8][9][10][11][12] or poromechanical coupling influence for rainfall-induced shallow landslides in unsaturated soils [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some macropores may connect to drainage tiles directly, creating an express path for water and chemicals (Malone et al, 2001;Fox et al, 2004). In general, accurate simulations of chemical transport in tile flow are dependent on accurate subsurface drainage (Malone et al, 2004a,b), and the latter is affected by rainfall intensity, soil matrix properties, and macroporosity (Fox et al, 2007;Nimmo, 2016;Que et al, 2018;Gao et al, 2018).…”
mentioning
confidence: 99%
“…Macropore flow velocity may be simulated by Poiseulle's law (Ahuja et al, 2000), kinematic wave (Que et al, 2018;Orozco-López et al, 2018), Stokes's law (Orozco-López et al, 2018), and power law (Jarvis et al, 1994). However, Gao et al (2018) found that Poiseulle's and the kinematic wave (Manning equation) overestimated macropore flow velocity.…”
mentioning
confidence: 99%